1985
DOI: 10.1136/oem.42.10.667
|View full text |Cite
|
Sign up to set email alerts
|

Body reactions during chain saw work.

Abstract: Body reactions during chain saw work were studied in 14 subjects. The subjects divided into three groups (control, sulpiride, and propranolol) possibility of vibration disease and cardiovascular diseases. None complained of Raynaud's phenomenon in the fingers, but some had slight numbness in the fingers and arms, palmar hyperhydrosis, or shoulder stiffness. The cumulative operation time was from 0920 to 1690.The subjects were divided into three groups: group I consisted of six control subjects, group 2 of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Two mechanisms have been suggested to induce a palmar sweating response as a result of such stress. One is associated with the central sympathetic nervous system (14) and the other with the sympathetic reflex (15). The changes in the saliva MHPG concentration observed in our study indicate that the palmar sweating response to whole-body vibration is probably due to the activation of the central sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 56%
“…Two mechanisms have been suggested to induce a palmar sweating response as a result of such stress. One is associated with the central sympathetic nervous system (14) and the other with the sympathetic reflex (15). The changes in the saliva MHPG concentration observed in our study indicate that the palmar sweating response to whole-body vibration is probably due to the activation of the central sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 56%
“…An elevated salivary cortisol concentration appeared to be only a transient effect as the trend showed a steady decline during the 2 h period after WBV. Previous studies have shown that cortisol responses to vibration and acceleration load are quite marked in humans (Matoba et al. , 1985) and animals (Perremans et al.…”
Section: Discussionmentioning
confidence: 99%
“…Vibration as a stressor may excite the higher centres of the sympathetic nervous system in the hypothalamus (Matoba et al 1985). In addition, vibration stress is thought to induce palmar sweating through the somatosympathetic reflex (Sato and Schmidt 1973).…”
Section: Discussionmentioning
confidence: 99%